A chromo-fluorogenic HMT sensor for Ag+ and the resultant HMT-Ag complex turn-off probe for F− in DMSO: experimental and theoretical studies. Issue 5 (May 2021) - Uahengo, Veikko; Endjala, Paulina; Naimhwaka, Johannes
Abstract: The photophysical properties of Hexamethylenetetramine (HMT ) were investigated through physical methods and spectroscopically in dimethyl sulfoxide (DMSO) at ambient temperature. Evidently, HMT turned out as a sensor, selective and sensitive to silver ion (Ag + ) only, among other cations, through colorimetric and fluorometric activities (observable by naked eye) and spectrally, both by UV-Vis and fluorescence spectroscopy. The resulting complex pedant (HMT-Ag ) is highly responsive to the presence of fluoride ion (F − ) in aqueous soluble DMSO, evidenced by changes in absorption spectra as well as fluorescence quenching, upon addition of the respective ions. Consequently, spectral changes induced by the addition of these ions, were consistently concomitant with colour changes, from colourless to light brown (HMT-Ag ) to dark brown (HMT-Ag-F ) in daylight condition, while bright light blue colour (HMT) to dark blue brownish (HMT-Ag) under UV-light conditions. The experimental results were complimented by theoretical studies, which are well within agreement of one another. Abstract : Hexamethylenetetramine, Silver and Fluoride ion probe, Colorimetric sensor, fluorometric sensor.